Psychometric Properties of Dunn\'s Sensory Profile School Companion - Guita Movallali; Abas Nesayan; Roghayeh Asadi Gandomani (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Sensory processing refers to reception, adjustment, and integration of sensory information sequentially and generates adaptive responses. People need to have appropriate sensory processing abilities for functioning adequately in the environment and be able to participate in activities of daily living. Dunn's sensory processing model consists of two constructions. The first construction involves neurological thresholds, and the second construction concerns self-regulation. When the two continuums are connected, four basic patterns of sensory processing appear. The four models are: sensation seeking (including representation of high thresholds and active self-regulation strategy), sensory avoiding (including representation of low thresholds and active self-regulation strategy), sensory sensitivity (including representation of low thresholds and passive self-regulation strategy), and low registration (including representation of high thresholds and passive self-regulation strategy). Sensory processing patterns can be seen in each age group from infancy to adulthood. These patterns are different for people with disabilities such as autism, attention deficit disorder/hyperactivity disorder, schizophrenia, Asperger syndrome, developmental disorders, and learning disabilities compared to those without disability. Dunn sensory profile school companion is provided to assess sensory processing patterns in children. As sensory processing plays an important role in the daily life of people, the purpose of this study was to determine the validity and reliability of Dunn's sensory profile school companion in children and students in the age group of 3-11 years. Materials & Methods The study was a descriptive-analytical one. The population consisted of all children and students aged between 3 and 11 years and studying in Tehran schools in the academic year 94-95 and those who attended preschools. The sample consisted of 384 children and students who were selected through multi-stage cluster sampling. Dunn's sensory profile companion was used to collect data. Dunn's sensory profile companion is a standardized measurement tool for assessing sensory processing abilities of children and students in the classroom and school and preschool environment. This tool was built by Winne Dunn. This profile are using for age range from 3 years to 11 years and 11 months and be completed by teachers and educators . Descriptive statistics such as mean and standard deviation were used for data analysis and confirmatory factor analysis, and Cronbach's alpha was used to draw inferences from the data. Results Confirmatory factor analysis was used to assess the validity of the sensory processing profile school companion. The results showed that sensory processing profiles are school companion and four factors had construct validity (P<0.001). Internal consistency (Cronbach's alpha) was used to evaluate the reliability. Cronbach’s alpha for the entire questionnaire was 0.879, and for sensory registration, sensation seeking sensory sensitivity and sensory avoiding was (0.818) (0.885), (0.825) (0.812), respectively. Thus, this confirms that the sensory processing profile school companion and four factors are reliable. Conclusion The results showed that Dunn's sensory profile has good reliability and validity. Dunn's sensory profile is a useful tool for assessing sensory processing patterns in school and kindergarten settings, and can be used by occupational therapists in clinical environments and by psychologists in educational environments. Information obtained from this profile can have diagnostic value and could also be used for the design of curriculum and classroom space.